Synthesis, crystal structure and magnetic property of one-dimensional heterometallic cyanide-bridged complex: {[Cu(hmpH)2Cu(hmp)(hmpH)Co(μ-CN)4(CN)2]·2H2O}n. (5th September 2016) - Sayın, Elvan; Kürkçüoğlu, Güneş Süheyla; Yeşilel, Okan Zafer; Taş, Murat; Öztürk, Mustafa; Yerli, Yusuf
Graphical abstract: The new hexacyanocobaltate(III) complex, {[Cu(hmpH)2 Cu(hmp)(hmpH)Co(μ-CN)4 (CN)2 ]·2H2 O} n (1 ) (hmpH = 2-pyridinemethanol), has been synthesized and characterized various techniques. The crystallographic data exposes that the complex crystallizes in the triclinic system and space group P 1 ¯ . In1, the Co(III) ions are six coordinated with six cyanide-carbon atoms in an octahedral arrangement. The Cu1 and Cu2 ions are coordinated with two cyanide-nitrogen atom, two nitrogen and two oxygen atoms from chelating two hmpH and hmpH/hmp ligands, respectively. The 2D layers were extended into 3D supramolecular networks by π⋯π and C–H⋯π interactions between pyridine rings of hmpH ligands. A magnetic study of1 shows a very small antiferromagnetic interaction within the chains through CN bridges. Abstract: A novel one-dimensional (1D) coordination polymer, {[Cu(hmpH)2 Cu(hmp)(hmpH)Co(μ-CN)4 (CN)2 ]·2H2 O} n (1 ) (hmpH = 2-pyridinemethanol), was synthesized and characterized by elemental analysis, spectral (FT-IR, Raman and EPR) methods, thermal analysis, single crystal X-ray diffraction and magnetic measurement techniques. In1, the Co(III) ions are six coordinated with six cyanide-carbon atoms in a octahedral arrangement. The Cu1 and Cu2 ions are coordinated with two cyanide-nitrogen atom, two nitrogen and two oxygen atoms from chelating two hmpH and hmpH/hmp ligands, respectively. The hmpH ligand in the complex has behaved as both anionic ligand (with its hydroxyl group being deprotonated) and as neutral form with the preserved OH group. The hydrogen bonding interactions between the crystal water molecules and hydroxyl group of hmpH ligands extends structure to the two dimensional (2D) supramolecular structure. The 2D layers were extended into 3D supramolecular networks by π⋯π and C–H⋯π interactions between pyridine rings of hmpH ligands. Variable temperature magnetic susceptibility measurement recorded in the 10–300 K range showed the presence of a very small antiferromagnetic within chains through CN bridges. Thermal stability and decomposition reactions of the complex take place in the temperature range 30–950 °C in a dry air atmosphere.